TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN RUMAH TANGGA GULA PASIR MEREK GULAKU DAN GMP DI KOTA BANDAR LAMPUNG - Sania, Beta; Adawiyah, Rabiatul; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The purpose of the study is to identify patterns of consumption and the factors that affect such patterns, satisfaction and loyalty of household consumers of granulated sugar brand Gulaku and Gula GMP in Bandar Lampung City. This research uses a survey method conducted in 10 supermarkets in Bandar Lampung City in March-April 2023. The total sample of 74 households was chosen by accidental sampling method. Descriptive analysis techniques, multiple linear regression analysis, the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and the loyalty pyramid were used to examine the research data. According to the findings, 1.72 kg of granulated sugar were consumed monthly by households  with the frequency of consumption was 30 times a month. The frequency of purchasing granulated sugar is 1 time per month and most consumers consume for their own consumption by consuming added to drinks and food. The consumer satisfaction score of the Gulaku is 81.58 percent and the Gula GMP is 81.70 percent which is included in the very satisfied category. Attributes that Gulaku and Gula GMP producers have to keep up are price, product hygiene, availability of expiration dates, halal labels and BPOM permits. Consumers of granulated sugar brands Gulaku and Gula GMP are in the category of satisfied buyer consumers.  Which means consumers feel satisfied with the product.